Pregnant Canadian Women Achieve Recommended Intakes of One-Carbon Nutrients through Prenatal Supplementation but the Supplement Composition, Including Choline, Requires Reconsideration. Issue 8 (10th June 2015) - Masih, Shannon P; Plumptre, Lesley; Ly, Anna; Berger, Howard; Lausman, Andrea Y; Croxford, Ruth; Kim, Young-In; O'Connor, Deborah L
Abstract: Background: Folate, vitamin B-6, vitamin B-12, and choline are involved in one-carbon metabolism and play critical roles in pregnancy including prevention of birth defects and promotion of neurodevelopment. However, excessive intakes may adversely affect disease susceptibility in offspring. Intakes of these nutrients during pregnancy are not well characterized. Objective: Our aim was to determine dietary and supplemental intakes and major dietary sources of one-carbon nutrients during pregnancy. Methods: In pregnant women ( n = 368) at ≤16 wk postconception, supplement use >30 d before pregnancy was assessed by maternal recall and supplement and dietary intakes in early (0–16 wk) and late pregnancy (23–37 wk) were assessed by food-frequency questionnaire. Results: Preconception, 60.1% (95% CI: 55.8, 64.3) of women used B vitamin–containing supplements. This increased to 92.8% (95% CI: 89.6, 95.2) in early and 89.0% (95% CI: 85.0, 92.3) in late pregnancy. Median supplemental folic acid, vitamin B-12, and vitamin B-6 were 1000 μg/d, 2.6 μg/d, and 1.9 mg/d, respectively. Forty-one percent and 50% of women had dietary intakes of folate and vitamin B-6 less than the estimated average requirement (520 mg/d dietary folate equivalents and 1.6 mg/d, respectively). Eight-seven percent of women had choline intakes less than the Adequate Intake (450 mg/d). Dietary intakes did not change appreciably during pregnancy. Fruits and vegetables and fortified foods contributed ∼57% to total dietary folate intake. Fruits and vegetables contributed ∼32% to total dietary vitamin B-6 intake and dairy and egg products contributed ∼37% to total dietary vitamin B-12 intake. Conclusions: Vitamin supplements were an important source of one-carbon nutrients during pregnancy in our sample. Without supplements, many women would not have consumed quantities of folate and vitamin B-6 consistent with recommendations. Given the importance of choline in pregnancy, further research to consider inclusion in prenatal supplements is warranted. This trial was registered at clinicaltrials.gov as NCT02244684.